2015
DOI: 10.1108/jsit-10-2014-0070
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation into the adoption of open source software in Information Technology outsourcing organizations

Abstract: Purpose – The purpose of this paper is to identify the influence of outsourcing on open-source software (OSS) and further investigate the factors that impact the adoption of OSS in global information technology (IT) outsourcing organizations serviced by Indian IT services organizations. Design/methodology/approach – The authors developed a conceptual model that describes the factors influencing the OSS adoption by using the technology-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…If the firm's senior management understands the advantages and usefulness that technologies can offer, they will be willing to help develop the capacity for 3DDT: infrastructure, management capabilities and employees' competence (Fosso et al , 2018; Martins et al , 2019). Other studies have shown that senior management support has a significant impact on a firm's adoption of information technologies (Hsu et al , 2014; Maduku et al , 2016; Ramanathan and Krishnan, 2015; Lorente-Martínez et al , 2020)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the firm's senior management understands the advantages and usefulness that technologies can offer, they will be willing to help develop the capacity for 3DDT: infrastructure, management capabilities and employees' competence (Fosso et al , 2018; Martins et al , 2019). Other studies have shown that senior management support has a significant impact on a firm's adoption of information technologies (Hsu et al , 2014; Maduku et al , 2016; Ramanathan and Krishnan, 2015; Lorente-Martínez et al , 2020)…”
Section: Discussionmentioning
confidence: 99%
“…If the firm's senior management understands the advantages and usefulness that technologies can offer, they will be willing to help develop the capacity for 3DDT: infrastructure, management capabilities and employees' competence (Fosso et al, 2018;Martins et al, 2019). Other studies have shown that senior management support has a significant impact on a firm's adoption of information technologies (Hsu et al, 2014;Maduku et al, 2016;Ramanathan and Krishnan, 2015;Lorente-Mart ınez et al, 2020) Subsequently, in the organizational dimension, technological competence was found to have a strong impact on the intention to adopt: as long as the 3D design digital technologies are compatible with the existing technological architecture, the likelihood of adoption will be higher (H3). Similarly, the results indicate that 3DDT adoption depends on technological competence in terms of organizational infrastructure, employees' technological training and technology-related experience (Alsaad et al, 2017;Chana and Chong, 2013;AlBar and Hoque, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Open Source Software (OSS) usage had previously been the preserve of programmers and software experts [5,6], but this 'second wave' [7] of OSS adoption by businesses and non-technical users has led to greater press and academic attention [8]. However, much of this attention has focused on OSS development methods and processes [9], with studies of adoption being under-represented [10][11][12][13]. This paper aims to partly address this gap through the achievement of the following objectives:…”
Section: Introductionmentioning
confidence: 99%
“…While there are numerous examples where these theories have been applied to studies of technology adoption (see [23] and [24] for OSS specific examples), there has been some criticism that this application has become formulaic, leading to a degree of stagnation [15]. Despite this criticism, there are few studies of OSS adoption [10][11][12], and this is an area where understanding remains limited [25].…”
Section: Introductionmentioning
confidence: 99%